Determinants of Quality of Nursing Work Life: A Systematic Review - Maf’ula, Dluha; Nursalam, Nursalam; Sukartini, Tintin (International Journal of Psychosocial Rehabilitation, 2025)
A large number of studies have addressed the detection of quality of nursing work life determinants, and the results are still inconclusive. This study aimed to systematically identify and review evidence regarding determinants of quality of nursing work life and to seek the reasons for contradicting results in relationships between determinants and quality of nursing work life in the literature to design a more robust measurement system for the quality of nursing work life. Methods: This systematic inclusion review followed the guidelines of the Preferred reporting items for Systematic reviews and Meta-Analysis (PRISMA) statement. The search was conducted in Scopus, EBSCO, Science Direct, and ProQuest. We used some search terms which were (‘predictors’ Or ‘determinants’ Or ‘factors affecting’ Or ‘measurements’ Or ‘dimensions’ Or ‘aspects’ Or ‘attributes’) AND (‘quality of nursing work life’)’. The search terms were adapted from previous review studies with the same purpose and general search in various data bases. We also manually searched for a list of relevant article references to identify additional publications. A total of 61 articles researching QNWL were identified. All quantitative, qualitative, and mixedmethods studies, including experimental, quasi-experimental, observational, review, and so on, were considered for the systematic review. Six, one and five papers had been published in Asia, America, and Europe. As we used broad inclusion and exclusion criteria to gather as many studies as possible, this attempt led us to have a huge amount of data to extract and synthesise. The number of documents that focus on nursing organizations’ factors (66.7%) was the most concerned sector. There were over 200 participants (83.3%) in significant studies. We found several determinants of QNWL investigated in a wide diversity of contexts. However, results varied as there is no globally accepted formulation of quality of nursing work life and measurement system.